Formative Research to Develop DC-SIPS: A Multilevel Intervention to Reduce Sugary Drink Intake and Promote Water Intake Among Black Youth in Washington, DC - Natalie Vallone; Nia I. Bodrick; Jasmine H. Kaidbey; Mariana F. Grilo; Shaleen Arora; Adam Dawer; Natasha Kumar; Jaiden Bluth; Natalie Lueders; Jennifer M. Sacheck; William H. Dietz; Karen A. McDonnell; et al. (Journal of Nutrition Education and Behavior, 2025)

Reconstructing the demographic history of orang‐utans using Approximate B ayesian Computation - Alexander Nater; Maja P. Greminger; Natasha Arora; Carel P. van Schaik; Benoit Goossens; Ian Singleton; Ernst J. Verschoor; Kristin S. Warren; Michael Krützen (Molecular Ecology, 2015)
Investigating how different evolutionary forces have shaped patterns of DNA variation within and among species requires detailed knowledge of their demographic history. O rang‐utans, whose distribution is currently restricted to the S outh‐ E ast A sian islands of B orneo ( P ongo pygmaeus ) and S umatra ( P ongo abelii ), have likely experienced a complex demographic history, influenced by recurrent changes in climate and sea levels, volcanic activities and anthropogenic pressures. Using the most extensive sample set of wild orang‐utans to date, we employed an Approximate B ayesian Computation ( ABC ) approach to test the fit of 12 different demographic scenarios to the observed patterns of variation in autosomal, X ‐chromosomal, mitochondrial and Y ‐chromosomal markers. In the best‐fitting model, Sumatran orang‐utans exhibit a deep split of populations north and south of L ake T oba, probably caused by multiple eruptions of the T oba volcano. In addition, we found signals for a strong decline in all S umatran populations ~24 ka, probably associated with hunting by human colonizers. In contrast, B ornean orang‐utans experienced a severe bottleneck ~135 ka, followed by a population expansion and substructuring starting ~82 ka, which we link to an expansion from a glacial refugium. We showed that orang‐utans went through drastic changes in population size and connectedness, caused by recurrent contraction and expansion of rainforest habitat during Pleistocene glaciations and probably hunting by early humans. Our findings emphasize the fact that important aspects of the evolutionary past of species with complex demographic histories might remain obscured when applying overly simplified models.

Heavily male‐biased long‐distance dispersal of orang‐utans (genus: Pongo ), as revealed by Y‐chromosomal and mitochondrial genetic markers - PIRMIN NIETLISBACH; NATASHA ARORA; ALEXANDER NATER; BENOIT GOOSSENS; CAREL P. Van SCHAIK; MICHAEL KRÜTZEN (Molecular Ecology, 2012)
Mating systems are thought to be an important determinant of dispersal strategies in most animals, including the great apes. As the most basal taxon of all great apes, orang‐utans can provide information about the evolution of mating systems and their consequences for population structure in this Family. To assess the sex‐specific population structure in orang‐utans, we used a combination of paternally transmitted Y‐chromosomal genetic markers and maternally transmitted mitochondrial DNA sequences. Markers transmitted through the more philopatric sex are expected to show stronger differentiation among populations than the ones transmitted through the dispersing sex. We studied these patterns using 70 genetic samples from wild orang‐utans from seven Bornean and two Sumatran populations. We found pronounced population structure in haplotype networks of mitochondrial sequence data, but much less so for male‐specific markers. Similarly, mitochondrial genetic differentiation was twice as high among populations compared to Y‐chromosomal variation. We also found that genetic distance increased faster with geographic distance for mitochondrial than for Y‐linked markers, leading to estimates of male dispersal distances that are several‐fold higher than those of females. These findings provide evidence for strong male‐biased dispersal in orang‐utans. The transition to predominantly female‐biased dispersal in the great ape lineage appears to be correlated with life in multimale groups and may reflect the associated fitness benefits of reliable male coalitions with relatives or known partners, a feature that is absent in orang‐utans.

Female philopatry and its social benefits among Bornean orangutans - Maria A. van Noordwijk; Natasha Arora; Erik P. Willems; Lynda P. Dunkel; Rahmalia N. Amda; Neneng Mardianah; Corinne Ackermann; Michael Krützen; Carel P. van Schaik (Behavioral Ecology and Sociobiology, 2012)

A multiplex-system to target 16 male-specific and 15 autosomal genetic markers for orang-utans (genus: Pongo) - Pirmin Nietlisbach; Alexander Nater; Maja P. Greminger; Natasha Arora; Michael Krützen (Conservation Genetics Resources, 2010)